14.3: The Relationship of Data Signal and Surface Noise in LTPS Products of Multiplexer Technology. (26th August 2021) - Tao, Jian; Feng, Shuai; Li, Yafeng; Peng, Zhong; He, Jian
Abstract : We have done a lot of work to study the surface noise of the panel due to the strict requirement of active stylus. During the research, we find that the surface noise occurs at the moment the mux circuits switch on, and the magnitude of positive noise is strongly dependent on what the panel display, in other words, the noise may have a strongly dependent on the data signal. Also the behavior of noise is consistent with that of common electrode. Then we established a circuit architecture to simulate the behavior of common electrode and found that the coupling of the data line on the common electrode would cancel each other out over a period of time while the existence of the mux circuits which breaks this balance. And based on this knowledge, we have done a lot of useful exploration and achieved good results.